History and Progress of Polymers for Energy Applications - Thalji, Mohammad R.; M. Ali, Gomaa A.; Chong, Kwok Feng (CRC Press, 2022)
Polymer materials have attracted the interest of researchers in recent years as electrode materials and electrolytes for a variety of energy applications such as supercapacitors, batteries, fuel cells, solar cells, and electrochromic devices. Over the last few decades, there has been a great deal of research into the potential applications of these materials. Conducting polymers, in particular, exhibit semiconductor-like properties, and they have emerged as fascinating materials for the fabrication of electronic devices. This chapter covers the history and progress of polymer materials in several energy applications divided into energy storage and energy conversion applications.